2022
DOI: 10.1038/s41598-022-24566-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum calcium level and in-hospital mortality in patients with acute myocardial infarction: a retrospective cohort study

Abstract: The association between serum calcium levels and the prognosis of patients with acute myocardial infarction (AMI) remains controversial. This study aimed to explore the association between serum calcium and in-hospital mortality in patients with AMI. The data of this study were extracted from the Philips eICU Collaborative Research Database. A total of 7284 patients were eventually enrolled in this study, of which 799 (10.97%) died during hospitalization. For each patient, serum calcium, corrected to albumin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Similarly, serum Ca level is an independent predictor of in-hospital death in patients with ST elevation myocardial infarction (STEMI) ( 29 ). Fang et al reported that both decreased and increased corrected serum Ca levels in AMI patients are associated with increased in-hospital mortality; moreover, patients with corrected serum Ca levels of 2.35 mmol/L showed the lowest risk of in-hospital death ( 30 ). As predictors of in-hospital mortality from AMI, most previous studies included either RDW or Ca; however, we also considered the ratio of RDW to Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, serum Ca level is an independent predictor of in-hospital death in patients with ST elevation myocardial infarction (STEMI) ( 29 ). Fang et al reported that both decreased and increased corrected serum Ca levels in AMI patients are associated with increased in-hospital mortality; moreover, patients with corrected serum Ca levels of 2.35 mmol/L showed the lowest risk of in-hospital death ( 30 ). As predictors of in-hospital mortality from AMI, most previous studies included either RDW or Ca; however, we also considered the ratio of RDW to Ca.…”
Section: Discussionmentioning
confidence: 99%